2021
DOI: 10.31014/aior.1993.04.02.208
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pilates Mat Exercises on self-rated health Levels, Body Mass Index and Flexibility in Middle Age Sedentary Women

Abstract: Goal: This study examines the effects of 10-week Pilates Mat exercises on body mass index (BMI), flexibility and self-rated health level in middle aged women. Method: The experimental group comprises middle aged female voluntary participants in the Pilates mat exercise program at Akdeniz University Sports Facilities in Antalya (n28), and the control group includes middle aged sedentary volunteers (n14). The experimental group members were given 60 minutes of Pilates mat exercise 3 days a week for 10 weeks. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Nevertheless, no such changes were seen in either group in this study after the eight weeks of Pilates training. Similar to our study, a lack of improvements in weight or BMI was reported in other Pilates training programs, such as in obese women, when comparing online and in-studio Pilates programs [57] and in sedentary middle-age women [58]. If participants in Pilates classes are interested in losing weight, their instructors should encourage them to also participate in aerobic training, in addition to Pilates.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, no such changes were seen in either group in this study after the eight weeks of Pilates training. Similar to our study, a lack of improvements in weight or BMI was reported in other Pilates training programs, such as in obese women, when comparing online and in-studio Pilates programs [57] and in sedentary middle-age women [58]. If participants in Pilates classes are interested in losing weight, their instructors should encourage them to also participate in aerobic training, in addition to Pilates.…”
Section: Discussionsupporting
confidence: 83%
“…Obesity; It is a risk factor for hypertension, hyperlipidemia, diabetes, cardiovascular diseases, some types of cancer and osteoarthritis (12,13). In addition, obesity reduces mobility and reduces the quality of life by preventing activities of daily living, making the individual dependent on a bed or chair (14). Overweight and obesity are modifiable conditions that can be prevented with lifestyle interventions to improve eating habits and increase physical activity.…”
Section: Introductionmentioning
confidence: 99%